Evaluation of the Pollution Elements at Samara Water Table – Iraq - Shimal, Marwah S.; Shaban, Auday H. (Iraqi Journal of Science, 2020)
Underground water is extracted by wells that are connected through underground canals. Thus, the levels of pollutant elements in ground water could be evaluated directly from water samples collected from the wells. This study was conducted in the city of Samara / Salah-Aldeen province – Iraq. The samples were taken from 29wells within the study area for the period 2012-2014 with a supervision from the General Authority for Groundwater / the Iraqi Ministry of Water Resources. GIS technology was adopted to calculate the pollution elements at Samara water table. The concentrations of chemical elements [K, Na, Mg, Cl, Ca] and compounds [SO4, HCO3] were manipulated and calculated for the entire area. The results of laboratory analyses showed that the groundwater in this area is not suitable for use as drinking water for humans, since the concentrations of the chemical elements and the compounds exceeded the permissible limits and are not in accordance with WHO standards. However, the results also indicated that the groundwater in the covered area is suitable for agriculture irrigation.